Bones of Contention: The Bonifacio Lectures - Ocampo, Ambeth R (Archīum Ateneo, 2014)
Bonifacio is only the beginning of a sad story, a story Filipinos refuse to accept. How the story ends remains in our hands. “FEAR history,” Bonifacio used to say “because in it none of your deeds can be hidden.” Unfortunately, history does not deal with the present nor with the future. History did not and could not protect Bonifacio from the assassins, the bullets and the bolos that killed him. Nevertheless, history continues to disturb Filipinos and will continue to do so until they learn this basic lesson—history does not repeat itself. We repeat history!